Exploring Early Detection of Frailty Syndrome in Older Adults: Evaluation of Oxi-Immune Markers, Clinical Parameters and Modifiable Risk Factors - Armanda Teixeira-Gomes; Blanca Laffon; Vanessa Valdiglesias; Johanna M. Gostner; Thomas Felder; Carla Costa; Joana Madureira; Dietmar Fuchs; João Paulo Teixeira; Solange Costa (MDPI AG, 2021)
Ageing is accompanied with a decline in several physiological systems. Frailty is an age-related syndrome correlated to the loss of homeostasis and increased vulnerability to stressors, which is associated with increase in the risk of disability, comorbidity, hospitalisation, and death in older adults. The aim of this study was to understand the relationship between frailty syndrome, immune activation, and oxidative stress. Serum concentrations of vitamins A and E were also evaluated, as well as inflammatory biomarkers (CRP and IL-6) and oxidative DNA levels. A group of Portuguese older adults (≥65 years old) was engaged in this study and classified according to Fried's frailty phenotype. Significant increases in the inflammatory mediators (CRP and IL-6), neopterin levels, kynurenine to tryptophan ratio (Kyn/Trp), and phenylalanine to tyrosine ratio (Phe/Tyr), and significant decreases in Trp and Tyr concentrations were observed in the presence of frailty. IL-6, neopterin, and Kyn/Trp showed potential as predictable biomarkers of frailty syndrome. Several clinical parameters such as nutrition, dependency scales, and polypharmacy were related to frailty and, consequently, may influence the associations observed. Results obtained show a progressive immune activation and production of pro-inflammatory molecules in the presence of frailty, agreeing with the inflammageing model. Future research should include different dimensions of frailty, including psychological, social, biological, and environmental factors.